2017
DOI: 10.1016/j.cub.2016.10.044
|View full text |Cite
|
Sign up to set email alerts
|

The Mitochondrial Lon Protease Is Required for Age-Specific and Sex-Specific Adaptation to Oxidative Stress

Abstract: Summary Multiple human diseases involving chronic oxidative stress show a significant sex bias, including neurodegenerative diseases, cancer, immune dysfunction, diabetes, and cardiovascular disease. However a possible molecular mechanism for the sex-bias in physiological adaptation to oxidative stress remains unclear. Here we report that Drosophila melanogaster females but not males adapt to hydrogen peroxide stress, whereas males but not females adapt to paraquat (superoxide) stress. Stress adaptation in eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
189
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 127 publications
(199 citation statements)
references
References 50 publications
10
189
0
Order By: Relevance
“…A prior study assessing H 2 O 2 -mediated adaptation, found 35-day old (‘middle-age’) females were no longer able to adapt [47]. Here, we sought to expand these findings and test the age-related changes in adaptation between 3 day (young) and 60 day (old) flies.…”
Section: Resultsmentioning
confidence: 92%
“…A prior study assessing H 2 O 2 -mediated adaptation, found 35-day old (‘middle-age’) females were no longer able to adapt [47]. Here, we sought to expand these findings and test the age-related changes in adaptation between 3 day (young) and 60 day (old) flies.…”
Section: Resultsmentioning
confidence: 92%
“…Adaptive homeostasis involves transient expansion of the physiological, or homeostatic, range of stress resistance that is typically reversed within hours. Major pathways for adaptive homeostasis include the Nrf2 signal transduction pathway in mammals (31), its CncC orthologue in flies (32), and its SKN-1 orthologue in worms (33). …”
Section: Transient Stress Adaptation: Hormesis and Adaptive Homeostasismentioning
confidence: 99%
“…Tra also regulates female-specific gene expression and differentiation through mechanisms that do not involve regulation of alternative splicing. For example, Tra-ON regulates the expression of a female-specific protein isoform of the mitochondrial protease Lon [6] . Finally, Sxl regulates sex-specific expression of additional targets including Notch.…”
Section: Sex Is a Critical Factor In Regulation Of Gene Expression Anmentioning
confidence: 99%
“…The resultant sex-specific autonomous cell differentiation then produces sex-specific hormones, including the steroid ecdysone, which further regulates sexual differentiation, reproduction, metabolism, and life span. Tra continues to be required to maintain sexual identify of cells in the adult, as over-expression or knockdown of Tra expression in the adult is sufficient to transform cells of the gut, fat-body, and other tissues to the opposite sex [6, 7] . In Drosophila , Y chromosome linked genes are required for normal spermatogenesis in the male.…”
Section: Sex Is a Critical Factor In Regulation Of Gene Expression Anmentioning
confidence: 99%
See 1 more Smart Citation